"Órfãos da mobilidade": as repercussões da migração da mãe na vida dos filhos que ficaram - Schuler, Flávia de Maria Gomes (2015)
The phenomenon of migration has increased around the world, highlighting the leading role of women in an area that traditionally was covered by men. It is estimated that half of migrants, worldwide, are women. In Brazil, this phenomenon has been common in the Northeast, which has up to 70% of female migrants. The overall objective of this thesis was to understand the experience and the repercussions of the mother's migration abroad in the lives of children who stayed. In this perspective we investigated the impact felt by children and their caregivers, from the mother's migration on; the feelings experienced and needs felt; the development of children in social, emotional/affective and academic aspects. Finally we identified the coexistence strategies established in the new reality and expectations for the future. Participated in this research seven teenagers (two brothers), of both sexes, aged between 13 and 18 years, children of women who migrated abroad, and six responsible for them, four grandparents, a father and an aunt. It is a research of qualitative nature, in which the following instruments were used: semi-structured interview, with two specific itineraries, one for teenagers and one for those responsible; adolescents was also applied the projective test of the Family Drawing. All instruments were conducted individually. The interviews were analyzed according to thematic content analysis and the drawing was analyzed according to the general, formal and content indicators. The results indicate that all teenagers have felt and continue to feel the impact of the migration of their mother. The emotional social development of all participants was altered in some way, one can observe feelings of sadness, abandonment, emotional ambivalence, and even revolt, isolation and resentment in some of them, despite the improving financial condition of the family propitiated by the mother. All children have difficulty in school, rebellious reactions to caregivers, and a child is involved in risky behavior, represented by use of alcohol and disregard for studies or work. However, one must consider other factors such as parental absence, in most cases; the lack of preparation for the migration would cause; successive changes within the family; the disapproval on the part of their own family or neighbors, because of the mother's decision to migrate. Most children maintain contact with the mother, by Internet or phone, and there have been two attempts at reunification that have gone wrong. Regarding expectations for the future, most of them want to form a traditional family, with mother, father and children, different from the family setting in which they currently live. All caregivers feel lost in conducting the rearing of these teens and burdened with this task, especially during adolescence, when there are several biopsychosocial changes. Analyses of the Family Drawing test confirmed what was found in the interviews. It is hoped that this research will give visibility to the family, especially the children, who remain in the country of origin, since the focus of most research turns to the individual who migrate.